Author Response: Burden of Chronic and Acute Conditions and Symptoms in People with Epilepsy. (22nd February 2022) - Bensken, Wyatt P.
Abstract : Thank you for your thoughtful comment on our article. 1 We agree that there is an important relationship between epilepsy and sleep. Sleep quality may even affect some of the conditions we examined, such as anxiety and mood disorders. Unfortunately, large health care data, which were used in this study, often does not prioritize these important aspects of health. The points raised here are certainly an important direction for future work and highlight the multifaceted health needs and priorities for people with epilepsy.